The Impact of Self-assessment on Enhancing EFL Learners' Writing Proficiency Case of: Second Year Bachelor Students of English at the University of Souk-Ahras - KADI Nardjes (My University, 2022)
Abstract Teachers of EFL use many methods and techniques to assess their learners in terms of the four skills. Self-assessment is one of those techniques. Since it defines the level of the learners by giving them the opportunity to assess their own progress and identify their weaknesses, strengths and take part in the learning process. The current study aims at investigating the impact of self-assessment technique on enhancing learners' writing proficiency in the department of English language at Mohamed Cherif Messaadia university in Souk Ahras. To test the main hypothesis that suggests the possibility of enhancing learners' writing proficiency through the application of self-assessment techniques both qualitative and quantitative methods (mixed method)were used in the data collection; a questionnaire was provided to second year EFL students. The gathered data have illustrated that the use of self-assessment has a positive impact in enhancing students' writing skill, by engagingthe learner in the teaching / learning process, and gives them the chance to be aware of their level and identify their weaknesses and strengths in order to fill in the gaps. According to the findings of this investigation the claimed hypothesis is confirmed.